KARAKTERISTIK MORFOLOGI UKURAN TUBUH KERBAU MURRAH DAN KERBAU RAWA DI BPTU SIBORONGBORONG - gerli hidayat (Universitas Sumatera Utara, 2013)
One way to determine the phenotypic diversity of buffaloes is through morphometric observations on each type of buffalo in Indonesia. Morphometric identification can be done by comparing the size and shape of the body. This study aims to obtain information related phenotypic morphometric characteristic of the body Murrah buffalo and swamp buffalo by Principal Component Analysis. The research was conducted in BPTU Siborongborong Kabupaten Tapanuli Utara on Juli up to September 2012. The reseach used 68 swamp buffalo (7 males, 61 females) and 32 Murrah buffaloes (5 males, 27 females) using a survey method. The results statistical showed that the body sizes of Murrah bufallo had higher variances than that Swamp bufallo. Body measurements were showed highly significant differences (P<0,01) in body length , shoulder height, hip height and chest circum, and no significant differences (P>0,05) for chest width, chest depth and hip width. The results principal component analysis showed that the size of the breeds are identifier through shoulder height and the shape is characterized from the chest width. The groups of data between the Murrah bufallo and the Swamp bufallo were significantly different for the shape, while for size has no different. It is concluded that the Murrah bufallo and the Swamp bufallo were significantly different for the shape while has no different for size. Keywords: Murrah Buffalo, Swamp Bufallo, Morphometrics, Principal Component Analysis.